A flame retardant polypropylene composite material for energy storage battery and preparation method thereof
By using carbon-coated molybdenum phosphide material and 9,10-dihydro-9-oxa-10-phosphophenol-10-oxide as composite flame retardants and combined with reinforcing fibers, the problem of flammability of polypropylene materials in energy storage batteries is solved, and high-efficiency flame retardant, good mechanical properties and environmentally friendly polypropylene composite materials are achieved.
Patent Information
- Application Number
- CN202510274883.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-10
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Polypropylene materials are flammable in energy storage battery applications and lack safety. Existing flame retardants release toxic gases during combustion, or affect the mechanical and processing properties of the material.
Carbon-coated molybdenum phosphide material and 9,10-dihydro-9-oxa-10-phosphophenol-10-oxide are used as composite flame retardant, combined with reinforcing fibers, and through specific preparation methods and process flows, a highly efficient flame-retardant polypropylene composite material is prepared.
The flame retardant performance of polypropylene composite materials is significantly improved, the limit oxygen index reaches or exceeds 30%, meets the V-0 flame retardant standards, and maintains good mechanical properties, processing performance and environmental friendliness.
Smart Images

Figure CN119752042A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of polymer material science and new energy technology, and more specifically, to a flame-retardant polypropylene composite material for energy storage batteries and a preparation method thereof. Background Art
[0002] As the global demand for clean energy and sustainable energy utilization grows, energy storage batteries, as a key link between energy production and consumption, are of great importance. Polypropylene (PP) is widely used in the shell, internal structural parts and diaphragms of energy storage batteries due to its low density, good mechanical properties, high chemical stability and low processing cost. However, polypropylene is a flammable material with a low limiting oxygen index (LOI). Once a fire occurs, it is easy to burn quickly and release a large amount of heat energy, which intensifies the spread of the fire and poses a serious threat to the safe operation of energy storage batteries.
[0003] In order to improve the flame retardant properties of polypropylene materials, researchers have tried a variety of methods, including adding halogen flame retardants, metal hydroxide flame retardants, phosphorus flame retardants, etc. However, although traditional halogen flame retardants have significant flame retardant effects, they release toxic gases during combustion and do not meet current environmental protection requirements; although metal hydroxide flame retardants are environmentally friendly, they are added in large quantities, which seriously affects the mechanical properties and processing properties of the material; phosphorus flame retardants are favored for their high flame retardant efficiency, low smoke and non-toxicity, but they are often difficult to achieve ideal flame retardant effects when used alone, and may affect the thermal stability and electrical properties of the material.
[0004] Therefore, developing a polypropylene composite material that can meet the requirements of high-efficiency flame retardancy while maintaining good mechanical properties, processing properties and environmental friendliness is of great significance for improving the safety of energy storage batteries and promoting the development of the new energy industry. Summary of the invention
[0005] The present invention provides a flame-retardant polypropylene composite material for energy storage batteries and a preparation method thereof, which solves the problems of flammability and insufficient safety of existing polypropylene materials in energy storage battery applications. Through innovative material design and preparation technology, comprehensive optimization of flame retardancy, mechanical properties, processing properties and environmental friendliness is achieved, providing key technical support for improving the overall safety performance of energy storage battery systems.
[0006] In a first aspect, the present invention provides a flame retardant polypropylene composite material for an energy storage battery, comprising the following raw materials in percentage by mass: Polypropylene resin 55%-70%, composite flame retardant 20-25%, reinforcing fiber 5%-20%; The composite flame retardant consists of carbon-coated molybdenum phosphide material and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
[0007] Preferably, the raw materials include the following mass percentages: 65%-70% polypropylene resin, 22%-25% composite flame retardant, and 15%-20% reinforcing fiber.
[0008] Preferably, the raw materials include the following mass percentages: 65% polypropylene resin, 22% composite flame retardant, and 16% reinforcing fiber.
[0009] Preferably, the molecular weight of the polypropylene resin is 80,000-150,000, the crystallinity of the polypropylene resin is 60%-70%, the ratio of the weight average molecular weight to the number average molecular weight Mw / Mn of the polypropylene resin is less than 2.4, and the melt flow rate is 1-50 g / 10 min.
[0010] Preferably, the reinforcing fiber is one or more of glass fiber, carbon fiber or aramid fiber; the length of the reinforcing fiber is 1-20 mm, and the diameter of the reinforcing fiber is 5-20 μm.
[0011] Preferably, the method for preparing the carbon-coated molybdenum phosphide material comprises the following steps: (1) adding ammonium molybdate to a nitric acid aqueous solution, stirring to dissolve, transferring to a reaction kettle, and performing a hydrothermal reaction to obtain molybdenum trioxide; (2) introducing the obtained molybdenum trioxide into a quartz glass boat, then placing the glass boat in a quartz tube, calcining in a high-purity nitrogen atmosphere, placing sodium hypophosphite in the upstream part of the gas, and calcining to obtain molybdenum phosphide; (3) The obtained molybdenum phosphide is placed in an ethanol solution of aniline, stirred and dispersed, centrifuged, and then calcined in a high-purity nitrogen atmosphere to obtain a carbon-coated molybdenum phosphide material.
[0012] Preferably, in step (1), the molar concentration of ammonium molybdate is 0.1-1.0 mmol, the concentration of the aqueous nitric acid solution is 55-70%, the volume of the reactor is 50-100 mL, the hydrothermal reaction temperature is 180-220° C., and the reaction time is 8-18 h.
[0013] Preferably, step (1) further comprises washing the product after the hydrothermal reaction with deionized water and ethanol, centrifuging, and drying.
[0014] Preferably, in step (2), the mass ratio of molybdenum trioxide to sodium hypophosphite is 0.5-3, the calcination temperature is 700-900° C., and the calcination time is 1.5-4 h.
[0015] Preferably, in step (3), the mass of molybdenum phosphide is 0.2-2 g, the volume ratio of aniline to ethanol is 0.5-1:1, the volume of ethanol is 10-20 mL, the stirring time is 1.0-10 h, and the calcination temperature is 500-700°C.
[0016] In a second aspect, the present invention provides a method for preparing a flame retardant polypropylene composite material for an energy storage battery, comprising the following steps: a) Premixing: polypropylene resin, composite flame retardant and reinforcing fiber are uniformly mixed in proportion, and premixed using a high-speed mixer for a mixing time of 5-30 minutes to obtain a premix; b) melt blending: putting the premix into a twin-screw extruder, setting the temperature, pressure and screw speed for melt blending, and obtaining a melt after melt blending; c) Extrusion granulation: the melt after melt blending is extruded through a die, solidified under water cooling or air cooling conditions, and cut into granules to obtain granules; d) Post-processing: drying and screening the particles.
[0017] Preferably, in step b), the temperature of melt blending is 180-260°C.
[0018] In summary, the present invention has the following beneficial effects: The flame retardant in the polypropylene composite material prepared by the present invention is molybdenum phosphide coated with a carbon layer (C@MoP). The introduction of the carbon thin layer can prevent acid from corroding the flame retardant and will not inhibit the flame retardant effect of the flame retardant. It is suitable for use as a flame retardant cover plate for lead-acid energy storage batteries. In addition, the use of carbon fiber can make the composite polypropylene material have good thermal conductivity and heat dissipation performance. Through the composite use of a specific proportion of a flame retardant system, reinforcing fibers, and synergists, the flame retardant performance, corrosion resistance, thermal conductivity and heat dissipation performance, mechanical properties, processing performance, and environmental friendliness are comprehensively improved.
[0019] The polypropylene composite material prepared by the present invention has high-efficiency flame retardancy. Through the coordinated use of a specific flame retardant system and a synergist, the limiting oxygen index (LOI) of the composite material is significantly improved to reach or exceed 30%, meeting the V-0 flame retardancy standard (according to UL94 test), effectively preventing the spread of fire and reducing the risk of fire; the composite material has excellent acid corrosion resistance. When the prepared sample is immersed in a sulfuric acid solution of a certain temperature and a certain concentration for a period of time, the appearance does not change, and the mass change rate of the sample is less than 2%, which proves that the sample has excellent acid corrosion resistance and can be used in energy storage devices such as lead-acid batteries.
[0020] The polypropylene composite material prepared by the present invention has good mechanical properties. The addition of reinforcing fibers significantly improves the tensile strength, flexural strength and impact toughness of the composite material. Even at a high flame retardant addition amount, the composite material can maintain good mechanical properties and excellent processing performance. The good processing characteristics of polypropylene, such as good melt fluidity, low molding temperature, easy injection molding and extrusion, are retained, and the composite material is suitable for the manufacture of battery components of various complex shapes.
[0021] The polypropylene composite material prepared by the present invention is environmentally friendly, and the selected flame retardants, synergists and reinforcing fibers are all environmentally friendly materials, complying with international environmental standards such as RoHS and REACH, reducing the impact on the environment, and having good thermal stability and electrical properties. By optimizing the flame retardant system and adding the synergist, the thermal stability and electrical properties of the composite material are guaranteed, and the composite material is suitable for the high temperature working environment and electrical insulation requirements of energy storage batteries.
[0022] The flame-retardant polypropylene composite material prepared by the present invention is particularly suitable for various energy storage batteries, including but not limited to the outer shells, internal structural parts (such as partitions, support frames), diaphragms and packaging materials of lithium-ion batteries, sodium-ion batteries, flow batteries, lead-acid batteries, etc. By improving the flame retardant performance and overall safety performance of the battery system, a safer and more reliable solution is provided for the fields of new energy vehicles, energy storage power stations, and household energy storage systems.
[0023] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope photograph of the carbon-coated molybdenum phosphide material C@MoP in the present invention. DETAILED DESCRIPTION
[0025] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0026] Example 1
[0027] A flame-retardant polypropylene composite material for energy storage batteries comprises the following steps: Step 1. Add 0.55 mmol of ammonium molybdate ((NH4)6Mo7O 24 ) was added into 70 mL of 65% nitric acid aqueous solution, stirred at room temperature for 2 hours until dissolved, transferred into a 100 mL reactor, and subjected to hydrothermal reaction at 180 °C for 12 hours. The product was centrifuged, washed and dried to obtain molybdenum trioxide (MoO3).
[0028] Step 2. Introduce MoO3 into a quartz glass boat, then place the glass boat in a quartz tube, and calcine it at 800°C in a high-purity nitrogen atmosphere for 3 hours. Add a certain amount of sodium hypophosphite (NaH2PO2) in the upstream part of the gas, and the mass ratio of MoO3 to NaH2PO2 is 1 to obtain molybdenum phosphide (MoP).
[0029] Step 3. Weigh 1.0 g of MoP into a quartz tube, measure 10 mL of aniline, dissolve in 15 mL of ethanol, stir for 4 h, centrifuge, and dry at 60 °C. The product is placed in a tube furnace and calcined at 500 °C for 1 h in a high-purity nitrogen atmosphere to obtain flaky C@MoP with a width of 0.3~0.7 μm.
[0030] Step 4. Premix the polypropylene resin, composite flame retardant and reinforcing fiber using a high-speed mixer, and control the mixing time to 5-30 minutes to ensure that each component is fully dispersed. The content of polypropylene resin is 60%, the addition amount of flame retardant is 25%, and the addition amount of reinforcing fiber is between 15%.
[0031] Step 5. Put the premix into a twin-screw extruder, set the temperature to 260°C, and the screw speed to 500 rpm for melt blending. Through the shearing action of the screw and high-temperature melting, the components are fully dispersed and uniformly formed into a uniform melt.
[0032] Step 6. Extrude the melt after melt blending through a die, solidify under water cooling or air cooling conditions, and cut into particles to obtain flame retardant polypropylene composite particles.
[0033] Example 2
[0034] Provided is a flame-retardant polypropylene composite material for an energy storage battery. Compared with Example 1, the difference is that in step 3, the stirring time is different, which is 2 hours, as shown in Table 1. Other experimental parameters and conditions are the same as those in Example 1.
[0035] Example 3
[0036] Provided is a flame-retardant polypropylene composite material for an energy storage battery. Compared with Example 1, the difference is that in step 3, the stirring time is different, which is 5 hours, as shown in Table 1. Other experimental parameters and conditions are the same as those in Example 1.
[0037] Example 4
[0038] Provided is a flame-retardant polypropylene composite material for an energy storage battery. Compared with Example 1, the difference is that in step 3, the stirring time is different, which is 10 hours, as shown in Table 1. Other experimental parameters and conditions are the same as those in Example 1.
[0039] Example 5
[0040] Provided is a flame-retardant polypropylene composite material for an energy storage battery. Compared with Example 1, the difference is that the ratio of the core-shell structure flame retardant C@CoP and the intumescent flame retardant is different, that is, the ratio is 10:15, as shown in Table 2, and the other experimental parameters and conditions are the same as those in Example 1.
[0041] Example 6
[0042] A flame-retardant polypropylene composite material for an energy storage battery is provided. Compared with Example 1, the difference is that the ratio of the core-shell structure flame retardant C@CoP and the intumescent flame retardant is different, that is, the ratio is 15:10, as shown in Table 2, and the other experimental parameters and conditions are the same as those in Example 1.
[0043] Example 7
[0044] A flame-retardant polypropylene composite material for an energy storage battery is provided. Compared with Example 1, the difference is that the ratio of the core-shell structure flame retardant C@CoP and the intumescent flame retardant is different, that is, the ratio is 20:5, as shown in Table 2, and the other experimental parameters and conditions are the same as those in Example 1.
[0045] Comparative Example 1 A flame-retardant polypropylene composite material for energy storage batteries comprises the following steps: Step 1. Add 0.55 mmol of ammonium molybdate ((NH4)6Mo7O 24 ) was added into 70 mL of 65% nitric acid aqueous solution, stirred at room temperature for 2 hours until dissolved, transferred into a 100 mL reactor, and subjected to hydrothermal reaction at 180 °C for 12 hours. The product was centrifuged, washed and dried to obtain molybdenum trioxide (MoO3).
[0046] Step 2. Introduce MoO3 into a quartz glass boat, then place the glass boat in a quartz tube, and calcine it at 800℃ in a high-purity nitrogen atmosphere for 3 hours. Put a certain amount of sodium hypophosphite (NaH2PO2) in the upstream part of the gas, and the mass ratio of MoO3 and NaH2PO2 is 1 to obtain molybdenum phosphide (MoP).
[0047] Step 3. Premix the polypropylene resin, flame retardant and reinforcing fiber using a high-speed mixer, and control the mixing time to 5-30 minutes to ensure that the components are fully dispersed. The content of polypropylene resin is 60%, the addition amount of flame retardant MoP is 15%, and the addition amount of reinforcing fiber is between 25%.
[0048] Step 4. Put the premix into the twin-screw extruder, set the temperature to 260℃, pressure and screw speed (adjust according to the equipment model and material characteristics), and perform melt blending. Through the shearing action of the screw and high-temperature melting, the components are fully dispersed and evenly formed into a uniform melt.
[0049] Step 5. Extrude the melt after melt blending through a die, solidify under water cooling or air cooling conditions, and cut into particles to obtain flame retardant polypropylene composite particles.
[0050] Comparative Example 2 A flame-retardant polypropylene composite material for energy storage batteries comprises the following steps: Step 1. Premix polypropylene resin, DOPO and reinforcing fiber using a high-speed mixer, and control the mixing time to 5-30 minutes to ensure that each component is fully dispersed. The content of polypropylene resin is 60%, the addition amount of flame retardant MoP is 15%, and the addition amount of reinforcing fiber is between 25%.
[0051] Step 2. Put the premix into the twin-screw extruder, set the temperature to 260°C, pressure and screw speed (adjust according to the equipment model and material characteristics), and perform melt blending. Through the shearing action of the screw and high-temperature melting, the components are fully dispersed and evenly dispersed to form a uniform melt.
[0052] Step 3. Extrude the melt after melt blending through a die, solidify under water cooling or air cooling conditions, and cut into particles to obtain flame retardant polypropylene composite particles.
[0053] The flame retardant polypropylene materials prepared in Examples 1-7 and Comparative Examples 1 and 2 were tested for peak heat release rate (PHRR), limiting oxygen index (LOI) and vertical burning (UL-94). The test results are shown in Tables 1 and 2.
[0054] Table 1 Performance test results of Examples 1-4
[0055] Table 2 Ingredient ratios and performance test results of Examples 2, 5-7 and Comparative Examples 1 and 2
[0056] According to the above preparation method, flame-retardant polypropylene composite material particles are obtained. After testing, the limiting oxygen index of the composite material is about 36%, reaching the V-0 flame retardant standard; after acid immersion, the mass loss rate is less than 0.1%; the tensile strength is 55MPa, the bending strength is 85MPa, and the impact toughness is 10kJ / m²; and it has good processability and is suitable for energy storage battery devices with high requirements on material appearance and mechanical properties.
[0057] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A flame-retardant polypropylene composite material for energy storage batteries, characterized in that: The following raw materials are included in mass percentage: Polypropylene resin 55%-70%, composite flame retardant 20-25%, reinforcing fiber 5%-20%; The composite flame retardant consists of carbon-coated molybdenum phosphide material and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.
2. The flame-retardant polypropylene composite material for energy storage battery according to claim 1, characterized in that: The molecular weight of the polypropylene resin is 80,000-150,000, the crystallinity of the polypropylene resin is 60%-70%, the ratio of the weight average molecular weight to the number average molecular weight of the polypropylene resin (Mw / Mn) is less than 2.4, and the melt flow rate is 1-50g / 10min.
3. The flame-retardant polypropylene composite material for energy storage battery according to claim 1, characterized in that: The reinforcing fiber is one or more of glass fiber, carbon fiber or aramid fiber; the length of the reinforcing fiber is 1-20 mm, and the diameter of the reinforcing fiber is 5-20 μm.
4. The flame-retardant polypropylene composite material for energy storage battery according to claim 1, characterized in that: The method for preparing a carbon-coated molybdenum phosphide material comprises the following steps: (1) adding ammonium molybdate to a nitric acid aqueous solution, stirring to dissolve, transferring to a reaction kettle, and performing a hydrothermal reaction to obtain molybdenum trioxide; (2) introducing the obtained molybdenum trioxide into a quartz glass boat, then placing the glass boat in a quartz tube, calcining in a high-purity nitrogen atmosphere, placing sodium hypophosphite in the upstream part of the gas, and calcining to obtain molybdenum phosphide; (3) The obtained molybdenum phosphide is placed in an ethanol solution of aniline, stirred and dispersed, centrifuged, and then calcined in a high-purity nitrogen atmosphere to obtain a carbon-coated molybdenum phosphide material.
5. The flame-retardant polypropylene composite material for energy storage battery according to claim 4, characterized in that: In step (1), the molar concentration of ammonium molybdate is 0.1-1.0 mmol, the concentration of the aqueous nitric acid solution is 55-70%, the volume of the reactor is 50-100 mL, the hydrothermal reaction temperature is 180-220° C., and the reaction time is 8-18 h.
6. The flame-retardant polypropylene composite material for energy storage battery according to claim 4, characterized in that: Step (1) also includes washing the product after the hydrothermal reaction with deionized water and ethanol, centrifuging, and drying.
7. The flame-retardant polypropylene composite material for energy storage battery according to claim 4, characterized in that: In step (2), the mass ratio of molybdenum trioxide to sodium hypophosphite is 0.5-3, the calcination temperature is 700-900°C, and the calcination time is 1.5-4h.
8. The flame-retardant polypropylene composite material for energy storage battery according to claim 4, characterized in that: In step (3), the mass of molybdenum phosphide is 0.2-2 g, the volume ratio of aniline to ethanol is 0.5-1:1, the volume of ethanol is 10-20 mL, the stirring time is 1.0-10 h, and the calcination temperature is 500-700°C.
9. The method for preparing the flame-retardant polypropylene composite material for energy storage battery according to any one of claims 1 to 8, characterized in that: The following steps are involved: a) Premixing: polypropylene resin, composite flame retardant and reinforcing fiber are uniformly mixed in proportion, and premixed using a high-speed mixer for a mixing time of 5-30 minutes to obtain a premix; b) melt blending: putting the premix into a twin-screw extruder, setting the temperature, pressure and screw speed for melt blending, and obtaining a melt after melt blending; c) Extrusion granulation: the melt after melt blending is extruded through a die, solidified under water cooling or air cooling conditions, and cut into granules to obtain granules; d) Post-processing: drying and screening the particles.
10. The method for preparing the flame-retardant polypropylene composite material for energy storage battery according to claim 9, characterized in that: In step b), the temperature of melt blending is 180-260°C.